Evaluation of Choroidal Thickness in Normal Eyes Using Enhanced Depth Optical Coherence Tomography - Harish; Shalini Singh; Manisha Agarwal; Rahul Mayor; Ramesh Venkatesh; Lokesh Chauhan (Delhi Journal of Ophthalmology)
Purpose: To evaluate the choroidal thickness in normal Indian population and to determine its correlation with age and refractive error Design: Cross sectional study conducted at a tertiary eye hospital in North India. Method: 512 eyes of256 normal subjects with no ocular pathology were enrolled. Choroidal scans were obtained for all the eyes using enhanced depth imaging (EDI) using spectral-domain optical coherence tomography(SD-OCT). Choroidal thickness measurements were made of the subfoveal choroid and at 500μ intervals from the fovea to 2.5mm nasal, 2.5mm temporal, 2.5mm superior and 2.5mm inferior from the centre of the fovea. Results: The mean subfoveal choroidal thickness observed in our study was 353.84±79μm. Mean choroidal thickness in the superior quadrant, inferior quadrant, nasal quadrant and temporal quadrant was 350.91±78 μm, 323.13±75μm, 294.25±70 μm and 335.33±73μm respectively. Subfoveal choroidal thickness was negatively correlated with age and refractive error indicating lesser subfoveal choroidal thickness with increasing age and myopia. Conclusions: Choroidal thickness varies with the distance from the fovea. Age and increase in myopia have a negative correlation with choroidal thickness.